Guduchi (tinospora cordifolia [wild.] miers) and its therapeutic external applications: A comprehensive review - Anu Joy; Buha Mital Mansukhbhai; Niral Hansrajbhai Sojeetra; R N Acharya (Wolters Kluwer Medknow Publications, 2021)
Background: Guduchi (Tinospora cordifolia [Wild.] Miers), family Menispermaceae, is widely distributed in India and is commonly known as Amrita. It is one of the most important medicinal plants used in Ayurveda. During COVID 19 pandemic situation, Guduchi gained a worldwide recognition for its therapeutic values in general and its immunomodulatory activities in particular through internal applications. Although highlighted for its external administration in various ayurvedic pharmacopoeias, information about its external applications is still lacking. Aim: The aim of the study was to prepare comprehensive data on external applications of Guduchi recorded in various ayurvedic texts. Materials and Methods: This review portrays external applications of Guduchi, from 25 classical texts of Ayurveda comprising 8 Samhitas (treatise), 11 Chikitsa Granthas (compendia of Ayurveda), and 6 Rasagranthas (compendia related to Rasashastra). Results: More than 141 formulations, having Guduchi as an ingredient, are used externally to combat almost 65 varied disease conditions. Among these diseased conditions, maximum are indicated for the management of Kushtha (integumentary diseases) followed by Sotha (edema), Netraroga (various eye diseases), Vrana (wound), Bhagandara (fistula-in ano), Jvara (fever), and Slipadha (filariasis), etc. The Guduchi external formulations are in 14 dosage forms. Conclusion: Present data may give insight to the researchers to probe into the external applications of the Guduchi which are not explored till date scientifically.